PENDIDIKAN KRITIS YANG MEMBEBASKAN: BELAJAR DARI PAOLO FREIRE - Agustinus Ryadi (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
Critical pedagogy is education that aims to fight oppression. Paolo Friere formulated the idea critical pedagogy in the book “Pedagogy of The Oppressed” as an eJort to deal with various forms of oppression and dehumanization and to seek a more humane education. Pedagogy of the oppressed is oriented towards full human self-actualization. Critical pedagogy is humane education that aims the full development of human beings to achieve their authenticity which is often hampered by repression and domination. With liberating education paradigm, critical pedagogy is diJerent from bank-model education where the teacher dominates the learning process and students only listen. Liberating education paradigm treats students as subjects and prioritizes problem-facing education. In critical education, the education process is directed at the awareness of oppression. Awareness of oppression is directed not only to the oppressed but also to the oppressors, because according to Freire the oppressors are oppressed people.